EVALUATION OF RISKS EMERGENCIES BY MODELLING THE FUNCTIONAL STATUS OF THE OBJECTS - Zatserkovnyy, V.; Зацерковний, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Here one can find the approach to develop a model of functional state of researched object for the assessment of the risks emergencies appearance. The analysis of the causes of appearance and development of natural and anthropogenic emergencies is conducted and the most indicative causes are defined. Emergency risk analysis is part of a system-wide approach to decision-making in the process of managing territories, procedures and practical measures to address the challenges of managing a security process. The basis of risk analysis is the physical and mathematical modeling of natural and socio-economic systems and processes occurring in them, which involves the interaction of the main components of the system with the environment in regular and extra-ordinary situations. Since dangerous phenomena (emergencies) occur in a certain area with specific coordinates, it is quite clear that geo-information systems (GIS) and geo-information technologies (GIS) are most appropriate for assessing the risk of emergencies. To describe the functioning of the monitoring object it is necessary to construct its mathematical model. The most complete state of the object of the study is characterized by its mathematical functional and statistical model (a system of equations that describes the dependence of the parameters of the monitoring object, its systems and subsystems on external and internal effects in the process of its functioning). Based on the analysis of this model, it becomes possible to formulate the main tasks that are solved by GIS in monitoring of natural or socio-economic systems, and synthesize the optimal structure of GIS.
Keywords: emergency situations; risk; risk assessment; model; geoinformation systems; geoinformation technologies